Les jardins familiaux franciliens entre urbanisation, végétalisation et agrarisation - Camille Robert-Boeuf (EchoGéo)
Allotment gardens are one of the oldest forms of urban gardening in France. In recent years, they are competing but also complementing other more recent forms of gardening such as community gardens or educational gardens. In Parisian region, these allotment gardens are part of the city because they associate several types of actors on several scales and underline issues of the urban planning. Originally involved in the urbanisation of the suburbs, they are now the victims of this urbanisation. However, more than a revegetation and an improvement of the living environment of the city, they promote a debated agrarisation of the metropolis.